The mind of Aristotle : a study in philosophical growth - Rist, John M. (Phoenix. Supplementary volume, 2018)
The author attempts to chart Aristotle's philosophical progress, using the techniques of both philology and philosophical analysis. His aim is to see where Aristotle came from philosophically and what impelled him to develop his ideas in particular directions. The first chapter is an overall account of Aristotle's philosophical activities as his life progressed; the remaining sections discuss in detail the development of such key themes as the possibility of metaphysics, activity and potentiality, categories, mind, substance, God, human nature and happiness, and the nature of society, including the proper role for women and the phenomenon of slavery.